Use of antipsychotic drugs and mood stabilizers in women of childbearing age with schizophrenia and bipolar disorder: epidemiological survey. (1st February 2013) - Barbui, C.; Conti, V.; Purgato, M.; Cipriani, A.; Fortino, I.; Rivolta, A. L.; Lora, A.
Abstract : Aims: To determine the prevalence of women of childbearing age with schizophrenia and bipolar disorder exposed to antipsychotic (AP) drugs and mood stabilizers (MS) in Lombardy, a European region of 10 million inhabitants and 1 752 285 women of childbearing age. Methods: The data concerning psychiatric care, drug treatments and pregnancy outcomes were retrieved from local administrative databases during a 12-month census period. Results: During a 12-month census period, 2893 women of childbearing age with schizophrenia (74.8% of all women of childbearing age with schizophrenia) and 918 with bipolar disorder (80.1% of all women of childbearing age with bipolar disorder) were exposed to AP drugs or MS, yielding a prevalence of exposure for women with schizophrenia of 1.65 (95% confidence interval (CI) 1.59–1.71) per 1000 female inhabitants, and for women with bipolar disorder of 0.52 (95% CI 0.49–0.55) per 1000 female inhabitants. Persistent exposure to potentially teratogenic medications accounted for one in every 1000 women of childbearing age. Of the 57 pregnancies in women with schizophrenia, normal delivery was recorded in 23 (40%) cases; of the 26 pregnancies in women with bipolar disorder, normal delivery was recorded in 10 (38%) cases. Conclusions: In women of childbearing age with severe mental disorders, exposure to psychotropic drugs is substantial, which suggests that the issue of reproductive health is epidemiologically relevant and a major public health concern.